2014
DOI: 10.1021/cn500001m
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 Receptor Activation Counteracts Adenosine A2A Receptor-Mediated Enhancement of Depolarization-Evoked [3H]-GABA Release from Rat Globus Pallidus Synaptosomes

Abstract: High levels of histamine H3 receptors (H3Rs) are found in the globus pallidus (GP), a neuronal nucleus in the basal ganglia involved in the control of motor behavior. By using rat GP isolated nerve terminals (synaptosomes), we studied whether H3R activation modified the previously reported enhancing action of adenosine A2A receptor (A2AR) stimulation on depolarization-evoked [(3)H]-GABA release. At 3 and 10 nM, the A2AR agonist CGS-21680 enhanced [(3)H]-GABA release induced by high K(+) (20 mM) and the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…The studies indicated that the sensor construct bound to histamine with nanomolar affinity (10 À5 M histamine, K d = 3.60 AE 0.06 nM; 10 À6 M, K d = 3.53 AE 0.05 nM; 10 À7 M, K d = 3.87 AE 0.11 nM; 10 À8 M, K d = 3.73 AE 0.04 nM; 10 À9 M, K d = 3.72 AE 0.06 nM, means AE SE, n = 5) ( Table 1). This is similar to the published K d values for histamine [44][45][46]. Furthermore, imetit with the H3 receptor sensor affinity was also calculated with nanomolar affinity (10 À5 M imetit, K d = 4.72 AE 0.06 nM; 10 À6 M, K d = 4.81 AE 0.07 nM; 10 À7 M, K d = 4.75 AE 0.03 nM; 10 À8 M, K d = 4.75 AE 0.01 nM; 10 À9 M, K d = 4.57 AE 0.06 nM, means AE SE, n = 5) ( Table 1).…”
Section: Agonist-induced Activation Of Intramolecular H3 Receptor Fresupporting
confidence: 90%
“…The studies indicated that the sensor construct bound to histamine with nanomolar affinity (10 À5 M histamine, K d = 3.60 AE 0.06 nM; 10 À6 M, K d = 3.53 AE 0.05 nM; 10 À7 M, K d = 3.87 AE 0.11 nM; 10 À8 M, K d = 3.73 AE 0.04 nM; 10 À9 M, K d = 3.72 AE 0.06 nM, means AE SE, n = 5) ( Table 1). This is similar to the published K d values for histamine [44][45][46]. Furthermore, imetit with the H3 receptor sensor affinity was also calculated with nanomolar affinity (10 À5 M imetit, K d = 4.72 AE 0.06 nM; 10 À6 M, K d = 4.81 AE 0.07 nM; 10 À7 M, K d = 4.75 AE 0.03 nM; 10 À8 M, K d = 4.75 AE 0.01 nM; 10 À9 M, K d = 4.57 AE 0.06 nM, means AE SE, n = 5) ( Table 1).…”
Section: Agonist-induced Activation Of Intramolecular H3 Receptor Fresupporting
confidence: 90%
“…In slices from rat SNr and striatum, the activation of dopamine D 1 receptors, coupled to Ga s proteins, enhances depolarization-evoked [ 3 H]-GABA release, and this effect is selectively counteracted by H 3 R-mediated inhibition of P/Qtype voltage-activated Ca 21 channels (Garcia et al, 1997;Arias-Montaño et al, 2001. Likewise, in the nerve terminals of striatopallidal neurons, H 3 R activation counteracts the facilitatory action of adenosine A 2A receptors (A 2A Rs), which are also coupled to Ga s proteins (Morales-Figueroa et al, 2014). H 3 R-mediated inhibition of GABA release has been observed in vivo in rat medial vestibular nucleus and in vitro in primary cultures of rat cerebrocortical neurons and dissociated neurons from the rat hypothalamus ventromedial nucleus (Jang et al, 2001;Bergquist et al, 2006;Dai et al, 2007).…”
Section: Function Presynaptic Effectsmentioning
confidence: 99%
“…Histamine also exerts multiple modulatory roles in basal ganglia circuits . For example, it activates medium spiny neurons, presynaptically inhibits glutamate release from corticostriate and thalamostriatal terminals, modulates the effects of dopamine and adenosine, inhibits serotonergic and GABAergic transmission in the substantia nigra pars compacta, antagonizes adenosine 2A receptor effects on GABA release from striato‐pallidal projections, and inhibits glutamate release in the globus pallidus . These multiple actions may contribute to differences in the motor manifestation of MSA and PD .…”
Section: Discussionmentioning
confidence: 99%
“…Histaminergic neurons of the tuberomammillary nucleus (TMN) have a major role in maintaining wakefulness, both as effectors of hypocretin neurons and by stimulating brainstem cholinergic and monoaminergic wake‐active neurons . Histamine also may have a modulatory role in basal ganglia circuits and may promote sympathoexcitatory responses via its projections to the rostral ventrolateral medulla …”
mentioning
confidence: 99%